ANALISIS PENDAPATAN USAHATANI JAMBU BIJI VARIETAS GETAS MERAH DI DESA PANYINGKIRAN, KECAMATAN PANYINGKIRAN, KABUPATEN MAJALENGKA - Nadyla Rizka Nur Amelia; Dini Rochdiani; Bobby Rachmat Saefudin (Universitas Galuh Ciamis, 2020)
One of the horticultural products widely consumed by the public is guava fruit. West Java is a province with the second largest number of red getas guava varieties produced in Indonesia. The purpose of this study is to know the costs of production, revenue, income, and ratio of revenue (R) and cost (C) that happened on red getas guava varieties in Desa Panyingkiran, Kecamatan Panyingkiran, Kabupaten Majalengka. This research was conducted in Desa Panyingkiran, Kecamatan Panyingkiran, Kabupaten Majalengka which is the center of production of red getas guava varieties in West Java. The design of this research is qualitative survey method. The sample of this research is 3 SOP farmers obtained through census and 50 Non SOP farmers obtained through the Slovin formula with a simple random method. The strata used in this study were based on the area of red getas guava varieties. The results showed that: (1) The results showed the farmer with the highest cash cost income is obtained by SOP farmer who use narrow land area it is Rp 209.805.922/Ha/year and Non SOP Farmer with medium land area it is Rp 100.858.775/Ha/year. While, the farmers with the highest total cost income is obtained by SOP farmers who use large land area it is Rp 165.429.758/Ha/year and Non SOP Farmers with medium land area it is Rp 64.39.333/Ha/year, and (2) The highest R/C of cash cost farmer is obtained by SOP farmer with large land area (R/C=17,1) and on Non SOP farmer with medium land area (R/C=4,6). While, the highest R/C of total cost farmer is obtained by SOP farmer with large land area (R/C=9,9) and on Non SOP farmer with medium land area (R/C=2,0).